2011
DOI: 10.1007/128_2011_294
|View full text |Cite
|
Sign up to set email alerts
|

Living in a Cage Is a Restricted Privilege

Abstract: There exist molecules, whose shape is reminiscent of a cage, that are able to include either metal ions or anions or both. In contrast to what happens in the macroscopic world, where a kinetic barrier prevents the escaping of the guest from the cage, the inclusion-extrusion of an ion from a molecular cage is in most cases thermodynamically controlled and the ion can get in or out of the cage at will. This gives the basis for highly selective ion recognition processes by cage-shaped ligands or receptors for met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Interference from sodium chloride isotonic solutions was reported to produce broader spots with larger retention factor of Kryptofix® 2.2.2, due to the presumable formation of the cryptand‐sodium ion complex 31 . In fact, the feasibility of the complex formation was confirmed by X‐ray diffraction characterization of the crystalline salt 32 . Halvorsen et al reported a fast and simple TLC spot‐test method for the determination of tetrabutylammonium or Kryptofix® 2.2.2 in 18 F‐labeled radiopharmaceuticals, using iodoplatinate‐impregnated TLC plates 25 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Interference from sodium chloride isotonic solutions was reported to produce broader spots with larger retention factor of Kryptofix® 2.2.2, due to the presumable formation of the cryptand‐sodium ion complex 31 . In fact, the feasibility of the complex formation was confirmed by X‐ray diffraction characterization of the crystalline salt 32 . Halvorsen et al reported a fast and simple TLC spot‐test method for the determination of tetrabutylammonium or Kryptofix® 2.2.2 in 18 F‐labeled radiopharmaceuticals, using iodoplatinate‐impregnated TLC plates 25 .…”
Section: Resultsmentioning
confidence: 95%
“…31 In fact, the feasibility of the complex formation was confirmed by X-ray diffraction characterization of the crystalline salt. 32 Halvorsen et al reported a fast and simple TLC spot-test method for the determination of tetrabutylammonium or Kryptofix ® 2.2.2 in 18 F-labeled radiopharmaceuticals, using iodoplatinate-impregnated TLC plates. 25 Following this procedure, we were able to analyze the residual Kryptofix ® 2.2.2 in [ 18 F]fluoropyridine-losartan formulations containing ascorbic acid.…”
Section: Thpta and Fluoropyridine-losartan Contentsmentioning
confidence: 99%
“…It is well accepted that the beauty of a molecular structure is often associated with its shape in Euclidean geometry (topography), but here we recognize that beauty can be associated with topology as well. 233 have also engaged the beauty of molecular knots in a chapter in a monograph 32 on Beauty in Chemistry. We refer the reader to these articles for further discussion on topological beauty.…”
Section: Topological Beautymentioning
confidence: 99%
“…Following an introduction to the mechanical bond across a variety of different settings, communities, and length scales, we will preview the range of this book's contents in the context of molecular aesthetics (Section 1.3), before finally offering a perspective (Section 1.4) on the evolution of mechanostereochemistry. The discussion in Sections 1.1-1.3, which is driven by the concept of beauty in chemistry, 32 is expanded upon and borrowed from, in part, our review 33 of mechanical bonds in the context of beauty, with permission from the publisher (copyright 2012 Springer-Verlag).…”
mentioning
confidence: 99%